Reflections on music, childhood, and school: creativity, agency and play in motion (Olhar de Professor, 2025)
This text assumes that music is a fundamental part of children’s cultures, as children express themselves through music and, through it, apprehend the world. The aim is to explore the pedagogical elements of the aesthetics of concrete music as an experimental form of engaging with sound, linking them to teaching and learning strategies for music in schools. We propose a dialogue between music education and the social studies of childhood, based on the analysis of two narratives that guide the construction of the theoretical argument. Finally, we present implications for pedagogical practice and for the continuing education of teachers, highlighting: the reflection on children’s participation and agency in their musical productions at school; and the development of greater tuning in the teacher-adult’s look and listening in relation to children’s musical expressions at school, through the strategy of bodily-musical play.
Keywords: Artistic activities; Teacher education; Teaching methodology